Risk Factors of Acute Respiratory Infection in Children Aged 6-12 Years in Urban Areas: A Literature Review Study - Rajebta, Nikita Alia; Arvian, Shenia Rully; Astuti, Winda Dwi; Tanca, Chendy Yugu; Herbawani, Chahya Kharin (Jurnal Ilmiah Kesehatan, 2025)
One disease that affects school-aged children is Acute Respiratory Infections (ARI). Acute Respiratory Infections (ARI) can be caused by various causative agents, such as viruses, bacteria, or even fungi; air pollution from smoke or gas can also cause Acute Respiratory Infections (ARI). The method used in preparing this article is a literature review. Article or journal searches were conducted on five databases: Mendeley, PubMed, ScienceDirect, Google Scholar, and Garuda. The keywords used in Mendeley, Google Scholar, and Garuda were "Faktor Risiko ISPA” AND “Anak", while PubMed and ScienceDirect used "risk factor" AND "acute respiratory infection" AND "child". Several risk factors exist for Acute Respiratory Infections (ARI) in children in urban areas. Environmental factors such as roofing, ventilation, and occupancy density are the risk factors for Acute Respiratory Infections (ARI) in urban school-aged children. Then, there are individual factors where age, gender, and other congenital diseases also affect the occurrence of ARI in children.